A content-based approach for scholarly journal recommendation - Gündoğan, Esra; Kaya, Mehmet (Ali KARCI, 2021)
In terms of the dissemination of academic information, it is very important that the articles written by the researchers are sent to the appropriate journals. The increase in the number of scholarly journals complicates the process of finding journals related to the field of research. Recommendation systems provide a great convenience for researchers in finding the right journals. Generally, user profile-based recommendation systems are not useful for new researchers. Considering this situation, a recommendation system is presented by considering only the content of the article entered by the user. The determination of the subjects of the journals, unlike other studies, was determined from the articles they had previously published. By comparing the similarities of the documents prepared for the journals and the article, suitable journals are recommended to the users. The results obtained from the recommendation system are compared with the results obtained from the recommendation tools of the journal publishers, and the success of the system has been evaluated. The system, covering many journals from different publishers, has performed well.

Akademik bilginin yayılımı açısından araştırmacılar tarafından yazılan makalelerin uygun dergilere gönderilmesi oldukça önemlidir. Bilimsel dergilerin sayısındaki artış araştırma alanına yönelik dergileri bulma sürecini zorlaştırmaktadır. Tavsiye sistemleri doğru dergileri bulma konusunda araştırmacılar için büyük kolaylık sağlamaktadır. Genellikle kullanıcı profiline özgü tavsiye yapan sistemler yeni araştırmacılar için kullanışlı değildir. Bu durum göz önünde bulundurulup sadece kullanıcı tarafından girilen makalenin içeriği dikkate alınarak gerçekleştirilen bir tavsiye sistemi sunulmaktadır. Dergilerin konu kapsamının belirlenmesi ise diğer çalışmalardan farklı olarak daha önceden yayınladıkları makalelerden belirlenmiştir. Dergiler için hazırlanan dokümanlar ile makalenin benzerlikleri karşılaştırılarak kullanıcılara dergi tavsiye edilmektedir. Tavsiye sisteminden elde edilen sonuçlar dergi yayıncılarının tavsiye araçlarından elde edilen sonuçlar ile karşılaştırılarak sistemin başarısı değerlendirilmiştir. Farklı yayıncılara ait birçok dergiyi kapsayan sistem iyi bir performans göstermiştir.
Bilimsel dergi tavsiyesi için içerik tabanlı bir yaklaşım
Keywords: Computer Software; Bilgisayar Yazılımı